Kedudukan Dan Perlindungan Terhadap Tenaga Kerja Pada Perusahaan Anak Dalam Perusahaan Grup/Holding Company (Studi Pada PT. Pusri Medan) - Melva Theresia Simamora; Budiman Ginting; Agusmidah Agusmidah; Mahmul Siregar (Iuris Studia: Jurnal Kajian Hukum, 2021)
The world of economy in Indonesia is growing, the number of business fields growing and competition between companies is increasing the need for broad thinking and not being fixated only on static conditions. Over time, Indonesia began to recognize holding companies which are the choice of many business in Indonesia. Holding companies are commonly held with the aim of holding economic control on a larger scale, eliminating competition or to ensure the stability of continuous supply of materials. This can be seen from the type of business of each company concerned, where the type of business is an interdependent vertical relationship between one and another company. The absence of legal regulations in the field of holding companies, the question arises what about the legal certainty of labor from a subsidiary company. Inadequate legal regulations regarding labor protection, especially in group companies, imply a legal vacuum in the world of labor protection. Based on the background of the problems regarding holding companies and labor aspects in the form of the holding companies that have been described, further and detailed research is needed. Where there is a legal vacuum on the protection of workers in holding companies. What laws and regulations and company policies are said to be sufficient and have protected the workers themselves in the business world in the form of holding companies.